2022
DOI: 10.3389/fnagi.2022.944697
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress-mediated memory impairment during aging and its therapeutic intervention by natural bioactive compounds

Abstract: Aging and associated neurodegenerative diseases are accompanied by the decline of several brain functions including cognitive abilities. Progressive deleterious changes at biochemical and physiological levels lead to the generation of oxidative stress, accumulation of protein aggregates, mitochondrial dysfunctions, loss of synaptic connections, and ultimately neurodegeneration and cognitive decline during aging. Oxidative stress that arises due to an imbalance between the rates of production and elimination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 133 publications
0
5
0
Order By: Relevance
“…It has been demonstrated that the Central Nervous System (CNS) can benefit from nutritional strategies and dietary interventions that prevent the signs of senescence, such as cognitive decline or neurodegenerative diseases such as Alzheimer’s disease and Parkinson’s Disease [ 100 ]. Both aging and associated neurodegenerative diseases are accompanied by the decline of several brain functions, including cognitive abilities, which are related to progressive deleterious changes at biochemical and physiological levels, leading to the generation of oxidative stress, disturbed protein metabolism with accumulation of protein aggregates, mitochondrial dysfunctions, loss of synaptic connections, and ultimately neurodegeneration and cognitive decline [ 101 ]. Because of its high energy demand, the brain is more susceptible to ROS-mediated damages, as it oxidizes lipids, proteins, and nucleic acids, thereby causing an imbalance in the homeostasis, and this especially occurs in the aging brain.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…It has been demonstrated that the Central Nervous System (CNS) can benefit from nutritional strategies and dietary interventions that prevent the signs of senescence, such as cognitive decline or neurodegenerative diseases such as Alzheimer’s disease and Parkinson’s Disease [ 100 ]. Both aging and associated neurodegenerative diseases are accompanied by the decline of several brain functions, including cognitive abilities, which are related to progressive deleterious changes at biochemical and physiological levels, leading to the generation of oxidative stress, disturbed protein metabolism with accumulation of protein aggregates, mitochondrial dysfunctions, loss of synaptic connections, and ultimately neurodegeneration and cognitive decline [ 101 ]. Because of its high energy demand, the brain is more susceptible to ROS-mediated damages, as it oxidizes lipids, proteins, and nucleic acids, thereby causing an imbalance in the homeostasis, and this especially occurs in the aging brain.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…A meta-analysis of randomized intervention trials reported that carotenoid interventions are associated with better cognitive performance [30]. Moreover, increased oxidative stress is believed to be associated with neurodegeneration and cognitive decline [31]. In a study of patients with recurrent depressive disorder, a higher concentration of plasma MDA was associated with worsened cognitive performance [32].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is plausible that the impaired memory observed in rats treated with a HFD may be attributed to elevated OS in the hippocampus, a brain region recognized for its role in cognitive regulation ( Jangra et al, 2014;Chahirou et al, 2018). In this context, several studies have identified elevated levels of OS in individuals experiencing memory dysfunction (Singh et al, 2022). Additionally, it is essential to highlight the increased susceptibility of this brain region to OS (Taniguti et al, 2018).…”
Section: Memory Impairment Following a Hfdmentioning
confidence: 99%